REPERCUSSIONS OF US PRESIDENT TRUMP'S STRATEGIES "2021_ 2017" FOR SETTLING THE PALESTINIAN ISSUE - WAFA S. H. DALOULL , DR. AMINURRAASYID BIN YATIBAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study aimed to present the repercussions of Trump’s strategy towards settling the Palestinian issue during his first term “2017-2021”, which was based on the “Deal of the Century” and the “Abraham Accords”, which led to dangerous turns that had negative effects on both the Israeli and Palestinian It extended to destabilizing the region, accompanied by global demonstrations, and reshaped international alliances far removed from the United States, thus setting the stage for radical changes at the political, diplomatic, and military levels in the Middle East. The study adopted the descriptive and analytical approach to present and analyze the most important pillars of President Trump’s strategies “2017-2021” towards settling the Palestinian issue, as well as the approach of the realist school in its offensive aspect to interpret the repercussions of Trump’s strategy for settling the Palestinian issue at the local, regional and international levels. The study concluded that President Trump's strategy"2017_ 2021" failed to achieve a peaceful settlement to the Palestinian issue due to the disregard for the Palestinian side and its demands. It also revealed that the US-Israeli regional alliance—the "Deal of the Century" and the "Abraham Accords"—did not bring security and prosperity to either the Palestinian or Israeli sides, but rather led to violence and destruction between them "Operation Al-Aqsa Flood, the Israeli massacre" On the Gaza Strip” and beyond to countries in the Middle East, President Trump’s strategy did not achieve its goal of integrating Israel economically and politically with the countries of the Middle East, but rather led to Israel’s international isolation, while the Palestinian issue emerged as a fundamental global issue that made most countries of the world recognize the establishment of the State of Palestine on the 1967 borders[1].The study recommended a set of measures centered on the necessity of Palestinian participation in any attempt to resolve the Palestinian issue, given their status as a principal party to the conflict.It also recommended the involvement of Arab and Islamic mediation in the Palestinian issue to reach a mutually acceptable solution between the two parties.